Between art and communication: a closer look to the first peruvians posters - Sánchez Flores, Miguel (2017)
The present article is an approximation to the first stage of the development of the Peruvian posters of the late fifties and sixties. The text is questioned on the two dimensions with which these first posters are born: communication and art, and also on the attempt to match precisely its esthetic dimension with its informative and commercial function. The text also identifies many of the first exponents, renowned graphic artists, who found in the design of posters, covers and commercial logos a space not only to develop their artistic practice but also a source of habitual income. Precisely, the article question those two dimensions —which do not seem to be faced in the beginning— and which agree favorably in the development of advertising graphics and also of Peruvian art. Finally, the article asks about the function of the poster and poses the hypotheses about what makes a poster transcend its informative function and make it remain in time as an object of collectible art, as happened with some of these first Peruvian posters.